Question #58780

2 Answers
Nov 1, 2017

RHS=(sin^2x)/(2+sin2xcscx)

=(2sin(x/2)cos(x/2))^2/(2+2sinxcosx xx1/sinx)

=(4sin^2(x/2)cos^2(x/2))/(2(1+cosx ))

=(4sin^2(x/2)cos^2(x/2))/(2*2cos^2(x /2))

=sin^2(x/2)=LHS

Nov 1, 2017

Formulas to be used in the proof.

  1. sin 2x = 2 sin x cos x

  2. sin (1/2 x)=+-sqrt((1-cosx)/2)
    :.sin ^2(1/2 x)=(1-cosx)/2

  3. cscx=1/sinx
  4. sin^2x+cos^2x=1
    sin^2x=1-cos^2x

Right Hand Side:

sin^2x/(2+sin2xcscx)=sin^2x/(2+2sinx cosx cscx)

=sin^2x/(2+2cancelsinx cosx * 1/cancelsinx)

=(1-cos^2x)/(2+2cosx )

=((1-cosx)(1+cosx))/(2(1+cosx ))

=((1-cosx)cancel(1+cosx))/(2cancel(1+cosx ))

=(1-cosx)/2

=sin^2(1/2)x

:.=Left Hand Side